Profiling olfactory stem cells from living patients identifies miRNAs relevant for autism pathophysiology. Issue 1 (December 2016) - Nguyen, Lam; Lepleux, Marylin; Makhlouf, Mélanie; Martin, Christelle; Fregeac, Julien; Siquier-Pernet, Karine; Philippe, Anne; Feron, François; Gepner, Bruno; Rougeulle, Claire; Humeau, Yann; Colleaux, Laurence
Abstract Background Autism spectrum disorders (ASD) are a group of neurodevelopmental disorders caused by the interaction between genetic vulnerability and environmental factors. MicroRNAs (miRNAs) are key posttranscriptional regulators involved in multiple aspects of brain development and function. Previous studies have investigated miRNAs expression in ASD using non-neural cells like lymphoblastoid cell lines (LCL) or postmortem tissues. However, the relevance of LCLs is questionable in the context of a neurodevelopmental disorder, and the impact of the cause of death and/or post-death handling of tissue likely contributes to the variations observed between studies on brain samples. Methods miRNA profiling using TLDA high-throughput real-time qPCR was performed on miRNAs extracted from olfactory mucosal stem cells (OMSCs) biopsied from eight patients and six controls. This tissue is considered as a closer tissue to neural stem cells that could be sampled in living patients and was never investigated for such a purpose before. Real-time PCR was used to validate a set of differentially expressed miRNAs, and bioinformatics analysis determined common pathways and gene targets. Luciferase assays and real-time PCR analysis were used to evaluate the effect of miRNAs misregulation on the expression and translation of several autism-related transcripts. Viral vector-mediated expression was used to evaluate the impact of miRNAs deregulation on neuronal or glial cells functions. Results We identified a signature of four miRNAs (miR-146a, miR-221, miR-654-5p, andmiR-656 ) commonly deregulated in ASD. This signature is conserved in primary skin fibroblasts and may allow discriminating between ASD and intellectual disability samples. Putative target genes of the differentially expressed miRNAs were enriched for pathways previously associated to ASD, and altered levels of neuronal transcripts targeted bymiR-146a, miR-221, andmiR-656 were observed in patients' cells. In the mouse brain, miR-146a, andmiR-221 display strong neuronal expression in regions important for high cognitive functions, and we demonstrated that reproducing abnormalmiR-146a expression in mouse primary cell cultures leads to impaired neuronal dendritic arborization and increased astrocyte glutamate uptake capacities. Conclusions While independent replication experiments are needed to clarify whether these four miRNAS could serve as early biomarkers of ASD, these findings may have important diagnostic implications. They also provide mechanistic connection between miRNA dysregulation and ASD pathophysiology and may open up new opportunities for therapeutic.